Perubahan indeks massa tubuh penderita tuberkulosis paru setelah mendapat obat antituberkulosis fase intensif - Triawantil Muhammad Fakhrurrozi, Cipta Waspada (Berita Kedokteran Masyarakat (BKM), 2005)
Background: Tuberculosis (TBC), a direct infectious disease, was affected by multifactorial such as malnutrition. Malnutrition often increases the risk of tuberculosis diseases and vice versa. The research was did to know the changes of body mass index (BMI) on tuberculosis patients with positive Acid-Fast Bacilli after treatment with antituberculosis drugs category 1 in intensive phase. The research used one group with pre- and post-test design. Method and Result: The research subjects were the tuberculosis patients with positive AFB who treat in puskesmas rujukan mikroskopis dan puskesmas pelaksana mandiri in district Banjar 2004. Data were collected by measuring the height and body-weight's patients before and after treatment. Nutritional status was state based on BMI. The results showed nutritional status before treatment was underweight (82.8%), normal (16.1%) and overweight (1.1%). After treatment, nutritional status changes to underweight (66.7%), to normal (31.1%) and to overweight (2.2%). Conclusion: The mean of body-weight before treatment was 39.49 kgs and after treatment changes to 41.97 kgs. The mean of BMI's patients before and after treatment were 16.39 and 17.44, respectively. Based on statistic test, it showed the bodyweight, BM! and nutritional status's patients before and after treatment were difference significantly